POTENSI ANTIOKSIDAN DAN ANTIHIPERLIPIDEMIA BUBUK KAKAO (Theobroma cacao L) FERMENTASI DAN NON FERMENTASI PADA TIKUS PUTIH (Rattus norvegicus Berkenhout, 1769) - , RINDA BINUGRAHENI, Dr.biol.hom. Nastiti Wijayanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is the 3rd largest cacao-producing country in the world. Based on the researchs, cocoa contain polyphenols (catechin, epicathecin, proantosianidin, and antisoanin), that potentially became antioxidant antihyperlipidemic. Polyphenols in cocoa powder depending on the quality and processing of cocoa beans. The aim of this study was to study antioxidant and antihyperlipidemic potential of fermented and unfermented cocoa powder in rats. Research design using RCD (Randomized Complete Design) factorial with eight treatment and three replication. Experimental rats divided into 8 group (control group, high lipid diet group, 3 unfermented cocoa-group, 3 fermented cocoa-group dose 1, 2, and 4 g /kg body weight). Rats were fed with high lipid diet for 8 weeks and cocoa powder was given orally for 4 weeks from 4 weeks later in experimental days. The level of body weight was measure at every week during experimental days and lipid profile was measure at 0, 4 and 8 weeks. Whereas malondialdehyde (MDA) level was measure at 4 and 8 weeks. The results showed the total phenolic content of fermented cocoa powder is greater than the unfermented cocoa powder. Fermented and unfermented cocoa powder decreased serum total cholesterol, LDL, triglicerides, and increased HDL levels. On the other hand, fermented of cocoa powder also can decreased serum MDA, but unfermented of cocoa powder canât decreased that. This result indicate that fermented cocoa powder is more potent as an antioxidant and antihyperlipidemic compared with unfermented cocoa powder.